Evaluating Inclusive Programs as an Effort to Provide Non-Discriminatory Education for Students with Special Needs - Hamam Zulkarnain; Syarah Bassalam (Innovative Journal of Educational Research and Insights, 2025)
Inclusive education represents a progressive effort to ensure equal learning opportunities for all students, including those with special needs, within mainstream educational settings. This study aims to evaluate the effectiveness of inclusive education programs using a mixed methods approach, combining both quantitative and qualitative data. Quantitative data were collected through standardized surveys assessing student academic outcomes, emotional well-being, and teacher preparedness. Meanwhile, qualitative data were obtained through in-depth interviews with teachers, school administrators, and parents, as well as direct classroom observations. The integration of these methods allowed for data triangulation, providing a comprehensive perspective on both the successes and challenges of inclusive education. Results show that inclusive programs positively influence students' social interaction and academic motivation; however, persistent barriers such as limited resources, insufficient teacher training, and systemic constraints hinder full implementation. The findings underscore the importance of continued program evaluation to identify best practices and areas needing improvement, ensuring that inclusive education not only remains a policy commitment but also becomes an effective, equitable, and sustainable educational practice.